Membangun Ekosistem Pembelajaran yang Mendukung Kesehatan Mental: Integrasi Psikologi Pendidikan dan Bimbingan Sosial - Ramadisha, Firlin; Putri, Aulia Rahma; Jais, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Student mental health is a crucial factor affecting the success of the learning process and psychosocial development. This study aims to examine the development of a learning ecosystem that supports mental health through the integration of educational psychology and social guidance. The method used is a literature review analyzing various sources related to educational psychology, social guidance, and mental health in the educational context. The findings indicate that the integration of these two fields creates an inclusive, supportive, and responsive learning environment to students’ psychological needs, thereby enhancing mental well-being, learning motivation, and academic achievement. This study emphasizes the importance of collaboration among educators, counselors, parents, and communities in building a holistic and sustainable learning ecosystem that supports student mental health.